Разложите на множетели:


а)а в куте — 125=
б)64+х в кубе=
в)а в квадрате-81=
г)n в кубе-25n=
Упростите выражение:
а)(3x+y)(x+y)-4y(x-y)=
б)(y-10)(y-2)+(y+4)(y-5)=
а)а в куте — 125=
б)64+х в кубе=
в)а в квадрате-81=
г)n в кубе-25n=
Упростите выражение:
а)(3x+y)(x+y)-4y(x-y)=
б)(y-10)(y-2)+(y+4)(y-5)=

A^3 — 125 = (a — 5)(a^2 + 5a + 25)
64 + x^3 = ( 4 + x)(16 — 4x + x^2)
a^2 — 81 = ( a — 9)(a + 9)
n^3 — 25n= n(n^2 — 25) = n( n — 5)(n + 5)

(3x + y)(x + y) — 4y( x — y) = 3x^2 + 3xy + xy + y^2 = 3x^2 + 4xy + y^2
( y — 10)(y — 2) + (y + 4)(y — 5) = y^2 — 12y + 20 + y^2 — y — 20 = 2y^2 — 13y

Добавить комментарий

Ваш e-mail не будет опубликован.